Calcification, Dissolution and Test Properties of Modern Planktonic Foraminifera From the Central Atlantic Ocean - Zarkogiannis, Stergios D.; Iwasaki, Shinya; Rae, James William Buchanan; Schmidt, Matthew W.; Mortyn, P. Graham; Kontakiotis, George; Hertzberg, Jennifer E.; Rickaby, Rosalind E. M. (Frontiers in Marine Science, 2022)
The mass of well-preserved calcite in planktonic foraminifera shells provides an indication of the calcification potential of the surface ocean. Here we report the shell weight of 8 different abundant planktonic foraminifera species from a set of core-top sediments along the mid-Atlantic ridge. The analyses showed that near the equator, foraminifera shells of equivalent size weigh on average 1/3 less that those from the middle latitudes. The carbonate preservation state of the samples was assessed by high resolution X-ray microcomputed tomographic analyses of Globigerinoides ruber and Globorotalia truncatulinoides specimens. The specimen preservation was deemed good and does not overall explain the observed shell mass variations. However, G. ruber shell weights might be to some extend compromised by residual fine debris internal contamination. Deep dwelling species possess heavier tests than their surface-dwelling counterparts, suggesting that the weight of the foraminifera shells changes as a function of the depth habitat. Ambient seawater carbonate chemistry of declining carbonate ion concentration with depth cannot account for this interspecies difference. The results suggest a depth regulating function for plankton calcification, which is not dictated by water column acidity.